Black oat grown with common vetch improves the chemical composition and degradability rate of forage - Fabiellen Cristina Pereira; Luiz Carlos Pinheiro Machado Filho; Daniele Cristina da Silva Kazama; Roberto Guimarães Júnior (Acta Scientiarum: Animal Sciences, 2020)
This study aimed to evaluate the effect of cultivating a combination of common vetch (Vicia sativa L.) with black oats (Avena strigosa Schreb.) on the chemical composition of forage and the grazing behavior of heifers. To accomplish this, two paddocks 2500m2 each from a Voisin Rational Grazing management system were divided into three blocks each and then into thirds (278m²) characterizing a randomized block design. Three different forage compositions were distributed into these thirds: oats grown alone, vetch grown alone, and oats grown with vetch. Forage samples were collected after 65 days through the square method. Right after collection, three groups of four heifers each grazed the plots for two hours in a 3x3 double Latin Square design for behavioral observation, grazing simulation through the hand-plucking method, and biting rate determination. Forage samples collected either by hand-plucking or the square method, were analyzed for chemical composition and “in vitro” degradability.  Statistical analyses were performed using the R package lme4. Data were evaluated with linear mixed-effects models. The inclusion of common vetch significantly increased forage production and oat protein content, but decreased the fiber content, which promoted better “in vitro” degradability. Grazing frequency was higher in pasture where oats were grown with vetch, but the biting rate was similar in all the three forage compositions evaluated. Forage collected by the square method did not differ from forage consumed by the heifers, probably meaning low herbage selectivity by heifers.  Furthermore, no interaction of investigated variables occurred between forage compositions and the method of collection. The inclusion of common vetch with black oats increased forage chemical composition, “in vitro” degradability, and forage production, thus having positive effects on the time cows spent grazing.